SEASONAL VARIATIONS OF NUTRIENT BUDGETS IN JAKARTA BAY, INDONESIA - Nugrahadi, Mochamad Saleh; Yanagi, Tetsuo; Tejakusuma, Iwan G.; Aji, Seno; Darmawan, Rahmania A. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
This study aims to quantify the fluxes of carbon, nitrogen, phosphorus, and silicate in Jakarta Bay and use these flux data to gain an initial understanding of the biogeochemical processes occurring in the system. We investigated water, suspended matter and sediments fluxes from estuarine, coastal water and outside of the bay. Water samples were analyzed for dissolved nutrients, chlorophyll-phytoplankton abundance, and their composition. Suspended matter and sediment were analyzed for carbon and nitrogen. Nutrient concentrations were high in the rivers or estuaries and then decreased rapidly seaward. Calculation budget results showed that Jakarta Bay is a sink for DIP, DIN and DSi during dry season and rainy season. In the dry season, the system is in the slightly fixation condition ([nfix-denit] = 0.03 mmol N m-2 d-1). In contrast, denitrification exceed nitrogen fixation ([nfix-denit] = -9.74 mmol N m-2 d-1) in the rainy season. Moreover, the bay produced net carbon about 2.6-32 mmol C m-2 d-1.